2018
DOI: 10.1007/s11051-018-4364-6
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the limits of synthetic macromolecular chemistry through Polyphenylene Dendrimers

Abstract: Polyphenylene dendrimers (PPDs) are a unique class of macromolecules because their backbone is made from twisted benzene repeat units that result in a rigid, shape-persistent architecture as reported by Hammer et al. (Chem Soc Rev 44:4072–4090, 2015) and Hammer and Müllen (Chem Rev 116:2103–210, 2016) These dendrimers can be synthetically tailored at their core, scaffold, and surface to introduce a wide range of chemical functionalities that influence their applications. It is the balance between the macromole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 114 publications
(180 reference statements)
0
20
0
Order By: Relevance
“…More recently, it has been reported that CNDP engineering of these shape-persistent PPD structures as a function of size, surface chemistry, architecture, etc. [191] allows these dendrimers to function as encapsulation hosts for a broad range of polar and non-polar guest molecules, as described in Figure 46. More specifically, it was found that when R=H, the PPD hosts were able to encapsulate small non-polar molecules (i.e., benzene, toluene, hexane, etc.).…”
Section: Engineering Size Shape Surface Chemistry Flexibility/rigimentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been reported that CNDP engineering of these shape-persistent PPD structures as a function of size, surface chemistry, architecture, etc. [191] allows these dendrimers to function as encapsulation hosts for a broad range of polar and non-polar guest molecules, as described in Figure 46. More specifically, it was found that when R=H, the PPD hosts were able to encapsulate small non-polar molecules (i.e., benzene, toluene, hexane, etc.).…”
Section: Engineering Size Shape Surface Chemistry Flexibility/rigimentioning
confidence: 99%
“…A structural comparison of (1) a rigid, shape-persistent (G1); poly(phenylene) dendrimer (PPD) to (2) flexible (G1); poly(propylenimine) (PPI) dendrimers and (3) flexible (G1); poly(amidoamine) (PAMAM) dendrimer[191].…”
mentioning
confidence: 99%
“…These dendrimers are internalized into cells while showing low toxicity both in vitro and in vivo and they possess the ability to transport lipophilic drugs within their nonpolar inner cavities . PPDs are unique because of the rigidity of their sterically demanding and space‐filling pentaphenyl‐benzene scaffold, and therefore provide persistent three‐dimensional structures . This class of dendrimer has the advantage that surface patterns can be exactly positioned since no backfolding of single dendritic arms (dendrons) can occur .…”
Section: Introductionmentioning
confidence: 99%
“…The invention of dendrimers, or cascade molecules, by Vögtle and Tomalia 40 years ago generated great enthusiasm in the chemistry community as a simple strategy to assemble synthetic macromolecules and polymers resembling the globular shape of proteins . The dendrimer concept, which consists in iteratively assembling dendrons into a regular molecular tree, was realized starting from a variety of building blocks such as benzyl alcohols, glycerols, phosphazenes, poly(amidoamides), polyphenylenes, and amino acids . The approach allowed designing microenvironment effects at the dendrimer core and multivalency effects at the dendrimer periphery, which proved useful in a variety of settings, most notably in catalysis and biomedical applications .…”
Section: Introductionmentioning
confidence: 99%